(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article provides a detailed understanding of individual rights, including the right to work. Labor law is one of the social rights of the individual and is regulated by labor legislation. Administrative and criminal liability arises for its violation. This article also examines the experience of Italy.